Pelaksanaan, Makna Dan Nilai Pada Tradisi Ngejot Tumpeng-Anten Di Desa Pekraman Kesian - Gita Widyantini, Pande Putu; Hartaka, I Made (Jayapangus Press, 2021)
Hinduism has many religious holidays, especially Balinese Hinduism. One of the holy religious holidays in Bali is Galungan. Galungan Day is usually greeted with a joyful atmosphere, this is because the philosophy of Galungan Day is the day when good (dharma) wins over evil (adharma). Speaking of traditions, the island of Bali itself has so many traditions that have been passed down from ancestors and are still preserved today. Likewise, when the Galungan holiday arrives, it will also be followed by the implementation of various traditions, one of which is the Ngejot Tumpeng-Anten tradition in the Kesian Pakraman Village. This research uses qualitative research. The results of this study indicate that the Ngejot Tumpeng-Anten tradition is a tradition that means togetherness between people, as a means of establishing relationships and silahturahmi with new couples. The implementation of this tradition is divided into two stages, namely right on Galungan day and on Galungan umanis. The difference between the first and second stages of ngejot lies in the time, the anten (bride) and the gift (jotannya). The tradition of Ngejot Tumpeng during Galungan is a tradition that has a high divine (theological) value, because it is a tradition related to faith in God Almighty. The use of offerings in Balinese terms called banten in this tradition is a form of self and also Ida Sang Hyang Widhi Wasa as the ruler of the maxrocosmos (bhuana agung) and microcosmos (bhuana alit) and also the universe. The values contained in this tradition, namely the value of togetherness, the value of mutual cooperation and the value of divinity / religion.